Effect of organic inhibitor on the corrosion behaviour of reinforced cement concrete. (2022) - Dharmaraj, R.; Narayanan, Karuppasamy; Ramalingam, Malathy; Vinodhini, P.; Rajalinggam, Pon
Abstract: Neem tree production results in a significant amount of garbage produced each year. Reduced environmental pollution as a result of neem seed coverage is necessary. In order to partially replace cement in concrete, the usage of Neem extract was researched. In this research work, the corrosion inhibitor impact that has been added to concrete of steel reinforcement by means of NEEM extract. NEEM extract helps to protect the steel reinforcement from corrosion and increase the lifetime of steel. The neem extract (organic) as an accelerator in concrete behalf of using the chemical admixture..In this research articles M25 grade of concrete was used. In the neem extract can add in concrete at various ratios percentage as 0 % (M0), 0.5 %(M1), 1 %(M2), 1.5(M3)%, and 2 %(M4).The mechanical test like compression test split tensile and flexural behavior test were performed at different curing days for various substitution of extract in concrete mix. The durability test like water absorption test was conducted after 28 days of curing. The strength properties shows good resistant against bending stress, it improves upto 14.08 % and 9.71 % for compressive and split tensile strength for 1 % substitution of extract, compared to control concrete mix. From the finding, substitution of NEEM extract shows good protection for concrete elements.